Analysis of real-time RT-PCR and rapid antigen test and its correlation with clinical characteristics, investigation profile, and imaging of SARI-suspected COVID-19 infections - Roshan Kanheya Lenka; Bhabani Patnaik; Jeetendra Ku Patra; Somi Patro; Dharitri Mohapatra; Nirupama Chayani; Mahadev Das (MGM Journal of Medical Sciences)
Background: Coronavirus disease 2019 (COVID-19) continues to be a significant global public health issue.